In Silico Analysis of Common Long Noncoding RNAs in Schistosoma mansoni and Schistosoma haematobium. (15th February 2021) - Sirekbasan, Serhat; Gurkok Tan, Tugba
Abstract : Background . Schistosomiasis caused by Schistosoma parasites is one of the most common parasitic infections worldwide. Genetic regulation of the genus Schistosoma, which has different developmental stages throughout its life, is quite complex. In these parasites, thousands of long noncoding RNAs (lncRNAs) estimated to be functional were identified. Identifying the transcripts expressed in common and detecting their functions for better understanding of the role of these lncRNAs require a comparative study. Methods . Assembled RNA-seq datasets belonging to S. mansoni and S. haematobium were obtained from the National Center for Biotechnology. A basic local alignment search tool (BLASTN) analysis was conducted against previously constructed lncRNA library to identify the common lncRNAs between two species. LncRNAs target genes and their gene ontology annotation was performed. Results . In S. mansoni and S. haematobium, 5132 and 3589 lncRNA transcripts were detected, respectively. These two species had 694 lncRNAs in common. A significant number of lncRNAs was determined to be transcribed from sex chromosomes. The frequently expressed lncRNAs appear to be involved in metabolic and biological regulation processes. Conclusions . These two species share similar lncRNAs; thus, this finding is a clue that they might have similar functions. In sexual development, they especially might play important roles. Our results will provide important clues to further studies about interactions between human hosts and parasites and the infection mechanisms of Schistosoma parasites.